2013
DOI: 10.1016/j.bpj.2012.11.3410
|View full text |Cite
|
Sign up to set email alerts
|

MCUR1 is an Essential Component of Mitochondrial Ca2+ Uptake that regulates Cellular Metabolism

Abstract: In dystrophic muscle, an increase in reactive oxygen species (ROS) production and sarcolemmal calcium (Ca 2þ) influx contributes to stretch-induced muscle damage however mechanistic insights into the activation of these pathways is lacking. In mdx myofibers (murine Duchenne muscular dystrophy), we have demonstrated that with mechanical stretch, the microtubule (MT) cytoskeleton is a critical mechano-transduction element for the activation of NADPH oxi-dase2 (Nox2) derived ROS production; a pathway we term X-RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 0 publications
4
88
1
3
Order By: Relevance
“…Although in these studies MCU was confirmed as the most dominant Ca 2ϩ influx mechanism (see also Ref. 42), interestingly, mitochondrial morphology, respiration, and cell viability remain normal in MCU knockout or MCU-overexpressing cells (4,17,52,67) even though Ca 2ϩ influx is critical in the regulation of these main mitochondrial functions. In addition, recent reports using mathematical analysis (81) and electrophysiological experiments (21) have suggested that cardiac mitochondria Ca 2ϩ influx through MCU might be slow and small under the physiological range of cytosolic Ca 2ϩ concentrations ([Ca 2ϩ ] c ; i.e., 0.1-20 M) compared with other cytosolic Ca 2ϩ fluxes such as sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA).…”
mentioning
confidence: 94%
“…Although in these studies MCU was confirmed as the most dominant Ca 2ϩ influx mechanism (see also Ref. 42), interestingly, mitochondrial morphology, respiration, and cell viability remain normal in MCU knockout or MCU-overexpressing cells (4,17,52,67) even though Ca 2ϩ influx is critical in the regulation of these main mitochondrial functions. In addition, recent reports using mathematical analysis (81) and electrophysiological experiments (21) have suggested that cardiac mitochondria Ca 2ϩ influx through MCU might be slow and small under the physiological range of cytosolic Ca 2ϩ concentrations ([Ca 2ϩ ] c ; i.e., 0.1-20 M) compared with other cytosolic Ca 2ϩ fluxes such as sarco(endo)plasmic reticulum Ca 2ϩ -ATPase (SERCA).…”
mentioning
confidence: 94%
“…VDAC1, a Ca 21 channel located at the mitochondrial outer membrane, allows the transfer of Ca 21 from the ER to the intermembrane space through a direct interaction with IP3-R. Subsequently, mitochondrial Ca 21 uptake 1 (MICU1) and MCUR1 transport Ca 21 from the intermembrane space to the lumen of mitochondria (Mallilankaraman et al, 2012a;Williams et al, 2013a). Inside the organelle, Ca 21 regulates the activity of three key dehydrogenases from the Krebs cycle, thus allowing normal ATP production.…”
mentioning
confidence: 99%
“…MICU modulates MCU function by physically interacting with it and serves as a gatekeeper in MCU-mediated mitochondrial calcium uptake. MICU ensures that mitochondria do not take up calcium into the mitochondria when cytoplasmic calcium levels are low (Csordas et al, 2013;Mallilankaraman et al, 2012). Unexpectedly, MCU-null mice do not exhibit any strikingly apparent phenotypes indicative of loss of mitochondrial calcium uptake (Herzig et al, 2013;Pan et al, 2013).…”
Section: Mitochondria Calcium and Ros: The Holy Trinitymentioning
confidence: 99%